Analysis of the luminous flux diffusion on the optical fiber lateral surface - Błaszczak, Urszula; Dorosz, Dominik; Dorosz, Jan; Dybczyński, Władysław; Zajkowski, Maciej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The method of the analysis of luminous flux diffusion on the lateral surface of an optical fiber as a basis for designing and manufacturing of side-hole optical fibers is presented. The idea of the controllable emission of the luminous flux by formation of the fiber lateral surface is described. The presented method was verified by manufacturing an optical fiber with controllable emission from the shaped lateral surface.
Optica Applicata, Vol. 39, 2009, nr 1, s. 63-76
Keywords: optyka; side-hole optical fiber; luminous flux; diffusion; shaped lateral surface